Early‐life epilepsy after acute symptomatic neonatal seizures: A prospective multicenter study. (2nd July 2021) - Shellhaas, Renée A.; Wusthoff, Courtney J.; Numis, Adam L.; Chu, Catherine J.; Massey, Shavonne L.; Abend, Nicholas S.; Soul, Janet S.; Chang, Taeun; Lemmon, Monica E.; Thomas, Cameron; McNamara, Nancy A.; Guillet, Ronnie; et al.
Abstract: Objective: We aimed to evaluate early‐life epilepsy incidence, seizure types, severity, risk factors, and treatments among survivors of acute neonatal seizures. Methods: Neonates with acute symptomatic seizures born 7/2015‐3/2018 were prospectively enrolled at nine Neonatal Seizure Registry sites. One‐hour EEG was recorded at age three months. Post‐neonatal epilepsy and functional development (Warner Initial Developmental Evaluation of Adaptive and Functional Skills – WIDEA‐FS) were assessed. Cox regression was used to assess epilepsy‐free survival. Results: Among 282 infants, 37 (13%) had post‐neonatal epilepsy by 24‐months [median age of onset 7‐months (IQR 3–14)]. Among those with post‐neonatal epilepsy, 13/37 (35%) had infantile spasms and 12/37 (32%) had drug‐resistant epilepsy. Most children with post‐neonatal epilepsy had abnormal neurodevelopment at 24‐months (WIDEA‐FS >2SD below normal population mean for 81% of children with epilepsy vs 27% without epilepsy, RR 7.9, 95% CI 3.6–17.3). Infants with severely abnormal neonatal EEG background patterns were more likely to develop epilepsy than those with mild/moderate abnormalities (HR 3.7, 95% CI 1.9–5.9). Neonatal EEG with ≥3 days of seizures also predicted hazard of epilepsy (HR 2.9, 95% CI 1.4–5.9). In an adjusted model, days of neonatal EEG‐confirmed seizures (HR 1.4 per day, 95% CI 1.2–1.6) and abnormal discharge examination (HR 3.9, 95% CI 1.9–7.8) were independently associated with time to epilepsy onset. Abnormal (vs. normal) three‐month EEG was not associated with epilepsy. Significance: In this multicenter study, only 13% of infants with acute symptomatic neonatal seizures developed post‐neonatal epilepsy by age 24‐months. However, there was a high risk of severe neurodevelopmental impairment and drug‐resistant seizures among children with post‐neonatal epilepsy. Days of EEG‐confirmed neonatal seizures was a potentially modifiable epilepsy risk factor. An EEG at three months was not clinically useful for predicting epilepsy. These practice changing findings have implications for family counseling, clinical follow‐up planning, and future research to prevent post‐neonatal epilepsy.